Trade, Foreign direct investment, and multinational enterprises in a general equilibrium model - Michael J. Koop (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Trade, foreign direct investment and the existence of multinational enterprises are often analyzed in separate model, which are frequently based on mutually exclusive assumptions. The paper integrates several features of international economic exchange into one general equilibrium model. This model explains various types of trade (interindustry, intraindustry, intrafirm), foreign direct investment (one-way, cross-hauling of FDI), and the existence of multinational enterprises (vertically as well as horizontally integrated ones). With the market structure being endogeneous, different production, trade and investment patterns can occur. In order to assess the influence of country asymmetries (relative and absolute factor endowment differences) and transport costs on production patterns as well as trade and investment flows, simulation techniques are applied to various specifications of the model.
Keywords: F12; F21; L11; 330; Außenwirtschaftstheorie; Direktinvestition; Multinationales Unternehmen; Allgemeines Gleichgewicht; Simulation; Theorie